AN ASSESSMENT OF THE APPROACH TO ADVENTURE BODILY PRACTICES IN SCHOOL PHYSICAL EDUCATION IN ILHEUS, BA - Tahara, Alexander Klein; Darido, Suraya Cristina [UNESP] (Univ Fed Rio Grande Do Sul, Escola Educ Fisica, 2018)
This qualitative research assessed Physical Education teachers of municipal and state schools of Ilheus, Bahia, regarding their approach to Adventure Body Practices (ABP), by evaluating their opinions on issues related to the inclusion of that content in class. A semi-structured interview containing four questions was used to collect data. It was applied to 18 teachers (ten men and eight women) aged 25-57, all of them with academic training in Physical Education. The data were examined by Content Analysis and the results indicated that most teachers were not aware of ABP and only four had already included such content in their classes. However, most teachers pointed out that strategies for including these practices in their classes are viable.
Keywords: Physical Education; Nature; School teachers